2019
DOI: 10.1111/mcn.12880
|View full text |Cite
|
Sign up to set email alerts
|

Lactation and maternal risk of diabetes: Evidence from the Mexican Teachers' Cohort

Abstract: One postpartum behaviour that may be protective against diabetes is lactation due to its potential role in resetting maternal metabolism after pregnancy. However, the role of lactation in maternal risk of diabetes has not been investigated in Latin American populations, where rates of breastfeeding are suboptimal and diabetes incidence is increasing. Therefore, our aim was to estimate the association between mean duration of lactation per child and maternal incidence of diabetes. We followed 66,573 women from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Ten studies were restricted to patients with a diagnosis of GD, whilst the remaining 12 included a mix of patients with and without GD, of which six stated the proportion of women with GD. Duration of lactation was classified differently across studies as (a) total lifetime duration of lactation, 13,24,26,32,34 (b) average duration of lactation per child, 24,26,28,33 (c) total duration for a single pregnancy in studies that followed up women after a specific pregnancy, 10,12,21,22,25,27,[29][30][31]35 and (d) lactation at hospital discharge. 14,23 Follow-up varied from 4 to 12 weeks for studies that evaluated the short-term association between lactation and type 2 diabetes after birth, and up to 25 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten studies were restricted to patients with a diagnosis of GD, whilst the remaining 12 included a mix of patients with and without GD, of which six stated the proportion of women with GD. Duration of lactation was classified differently across studies as (a) total lifetime duration of lactation, 13,24,26,32,34 (b) average duration of lactation per child, 24,26,28,33 (c) total duration for a single pregnancy in studies that followed up women after a specific pregnancy, 10,12,21,22,25,27,[29][30][31]35 and (d) lactation at hospital discharge. 14,23 Follow-up varied from 4 to 12 weeks for studies that evaluated the short-term association between lactation and type 2 diabetes after birth, and up to 25 years.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12]22 Studies with a longer follow-up showed a protective association between lactation and the RR of type 2 diabetes, with a stronger association in women with GD than in those without GD. 13,[31][32][33] The extent of the benefit seemed to increase in parallel with duration of lactation and to be independent of well-established risk factors for type 2 diabetes, such as obesity, ethnicity, diet, exercise, weight gain and antecedent metabolic risk profiles. 24,28,34 Meta-analysis of studies that compared ever with never lactation 14,[21][22][23][24][25][26][27][28][29][30][31] suggested that lactation was associated with a 27% lower risk of type 2 diabetes (RR 0.73, 95% CI [0.65, 0.83]) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, feeding infants with infant formula has a deleterious effect on their health (Anttila‐Hughes, Fernald, Gertler, Krause, & Wydick, 2018; Mameli et al, 2016). Breastfeeding has important health benefits for the mother who breastfeeds (Chowdhury et al, 2015; Mazariegos et al, 2019; Unar‐Munguia, Torres‐Mejia, Colchero, & Gonzalez de Cosio, 2017), and only a small percentage of women are unable to breastfeed (~5%) due to serious disease or adoption (Lawrence & Lawrence, 2005).…”
Section: Introductionmentioning
confidence: 99%